Patients Presenting with a Hot, Swollen Joint: A Single-Centre Retrospective Analysis - Chisari, Emanuele; Yaghmour, Khaled M.; Peat, Fidel; Khan, Wasim (Current Rheumatology Reviews, 2020)
Background: A hot, swollen joint is a common clinical condition encountered in the ED and elective orthopaedic and rheumatology clinics. These patients can be difficult to manage and properly treat. Aims and Objectives: The aim of this study was to report a single centre retrospective analysis of patients presenting to our institution for a hot, swollen joint over a three-month period. Methods: The study included patients presenting with a hot, swollen joint to ED or electively to clinics. The synovial fluid was aspirated and sent for microbiological and cytological investigation. P value was set to < 0.001. 36 patients (22 M, 14 F) with a mean age of 72.8 ± 17.4 years met our criteria. 20 cases (55.6 %) involved the knee joint, the wrist in 10 cases (27.8%), the elbow in 3 cases (8.3%) and the shoulder in 3 cases (8.3%). Results: Of the 36 synovial fluid samples collected, only 7 (19.4%) reported evidence of infection. On cytological examination of the synovial fluid, 21 (58.3%) reported presence of calcium pyrophosphates crystals (Pseudogout), 4 (11.1 %) reported presence of uric acid crystals (Gout) and 11 (30.5%) reported absence of crystals. We found a significant correlation between age and the diagnosis of pseudogout and between previous antibiotic treatment and ED presentation. Our study sheds light on the high incidence of crystal-related pathologies. Conclusion: In order to improve our management of this common condition and enhance our understanding of the clinical diagnosis in certain patient population, further high-profile clinical studies are needed.
Keywords: monoarthritis